2023
DOI: 10.3390/toxics11080705
|View full text |Cite
|
Sign up to set email alerts
|

Gourmet Table Salts: The Mineral Composition Showdown

Eleonora Di Salvo,
Roberta Tardugno,
Vincenzo Nava
et al.

Abstract: Table salts with their specialty flake size, textures, flavors, and colors can be considered a gastronomy niche food already increasing in demand worldwide. Being unrefined, they can contain trace elements potentially both healthy and toxic. In this study, 12 mineral elements (Al, Ca, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Se, and Zn) in 10 different salts commercially available in southern Italy namely, Atlantic grey, Baule volante, Guerande, Hawaiian pink, Hawaiian black, Himalayan pink, Maldon, Mozia, Persian blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In a study by Ref. [ 69 ] on metal contaminants Tehran in edible salts, Pb (1.59 ± 0.90), Cd (0.91 ± 0.32), Zn (6.02 ± 2.54), Fe (17.8 ± 6.11), Cu (1.24 ± 0.90), and Al (5.82 ± 0.61) mg/Kg in salts were Pb (0.86 ± 0.52), Cd (0.65 ± 0.34), Zn (6.5 ± 4.86), Fe (15.3 ± 5.95), Cu (1.21 ± 0.79), and Al (5.60 ± 0.75) mg/Kg in table salts [ 8 ]. study on the mineral composition showed that the composition of copper (Cu) in Mozia and Persian blue salt was 41.63 ± 4.18 mg/kg and 50.61 ± 6.19 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study by Ref. [ 69 ] on metal contaminants Tehran in edible salts, Pb (1.59 ± 0.90), Cd (0.91 ± 0.32), Zn (6.02 ± 2.54), Fe (17.8 ± 6.11), Cu (1.24 ± 0.90), and Al (5.82 ± 0.61) mg/Kg in salts were Pb (0.86 ± 0.52), Cd (0.65 ± 0.34), Zn (6.5 ± 4.86), Fe (15.3 ± 5.95), Cu (1.21 ± 0.79), and Al (5.60 ± 0.75) mg/Kg in table salts [ 8 ]. study on the mineral composition showed that the composition of copper (Cu) in Mozia and Persian blue salt was 41.63 ± 4.18 mg/kg and 50.61 ± 6.19 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Salt is a ubiquitous dietary component consumed worldwide for human health and nutrition [ [4] , [5] , [6] ]. However, the quality and mineral content of salt vary significantly depending on its source [ 7 ], storage conditions [ 8 ], production, and processing methods [ [9] , [10] , [11] ]. Several studies have examined the mineral content of salt and its implications for human health [ [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hg analysis was performed using DMA-80 (Milestone S.r.l., Sorisole, Italy), a direct mercury analyser of solid, liquid, and gas samples. The DMA-80 was used according to the previous study by [ 43 ]. Overall, 0.1 g of each algae sample and 100 µL of each seawater sample were placed in a nickel cuvette and quartz cuvette, respectively, and then subjected to a temperature ramp from 60 °C to 650 °C for approximately 5–6 min.…”
Section: Methodsmentioning
confidence: 99%